2011
DOI: 10.4269/ajtmh.2011.10-0261
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response against P2β from Trypanosoma cruzi in Persons with Chronic Chagas Disease: Its Relationship with Treatment Against Parasites and Myocardial Damage

Abstract: We investigated the relationship between potentially pathogenic antibodies against a Trypanosoma cruzi ribosomal protein (P2β) and the evolution of Chagas disease and the effect of trypanocidal treatment on these variables. Seventy-eight patients with chronic Chagas disease who were followed-up for more than 20 years were divided into three groups: 30 asymptomatic persons undergoing specific treatment (group A), 37 asymptomatic persons not undergoing specific treatment (group B), and 11 patients with chronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Among these patients, 12 (54.5%), 11 (39.3%), and 5 (31.3%), met the STEC. The observed predictive value of the BMK set at an early time point is relevant, since other studies have shown complete or partial seroconversion after periods of time that were five times longer than those in the present study (19,34,40). Furthermore, as stated by the TPP, this set of four biomarkers meets the requirements to be considered an acceptable biomarker for evaluating potential therapeutic efficacy in chronic indeterminate Chagas disease patients.…”
Section: Discussionsupporting
confidence: 52%
“…Among these patients, 12 (54.5%), 11 (39.3%), and 5 (31.3%), met the STEC. The observed predictive value of the BMK set at an early time point is relevant, since other studies have shown complete or partial seroconversion after periods of time that were five times longer than those in the present study (19,34,40). Furthermore, as stated by the TPP, this set of four biomarkers meets the requirements to be considered an acceptable biomarker for evaluating potential therapeutic efficacy in chronic indeterminate Chagas disease patients.…”
Section: Discussionsupporting
confidence: 52%
“…Nonetheless, ongoing efforts for the identification of additional biomarkers are underway, including electrocardiographic, immunologic and biochemical markers, which may greatly improve and facilitate the monitoring of Chagas disease progression and thus vaccine evaluation. [86][87][88][89][90][91][92] As indicated above, a successful vaccine will need to induce a strong cellular immune response, with the activation of CD8 + cytotoxic T cells in order to effectively control T. cruzi parasites. This requirement places some constraints on the formulations and types of vaccines that may be used, since such a response is harder to induce than a humoral response.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The same group has recently evaluated the levels of specific antibodies against the ribosomal protein TcP2β, as a cure marker. (Fabbro et al, 2011) Their results showed a significant decrease of specific anti-TcP2β in sera from treated patients, although no negative results occurred, which is a similar behavior than that displayed when performing conventional serology. Therefore, anti-TcP2β does not resemble to be an apparently good candidate to be used as an early marker of the infection cure.…”
Section: Laboratory Treatment Monitoringmentioning
confidence: 64%
“…(Breniere et al, 2002) In a longitudinal evaluation of asymptomatic and cardiac groups of patients, we described that only the individuals who evolved to a more severe clinical status increased specific anti-TcP2 concentration in late stages of the infection. (Fabbro et al, 2011) However, the transversal comparison of the sera from patients with and without cardiopathy revealed that anti-TcP2 concentration between both groups was not significantly different. The discrepant results mentioned above show that it is not still clear if anti-TcP2 can be used as a serological marker of myocardic damage.…”
Section: Chronic Infection Monitoringmentioning
confidence: 86%